Long Term High Fat Diet Treatment: An Appropriate Approach to Study the Sex-Specificity of the Autonomic and Cardiovascular Responses to Obesity in Mice - Bruder-Nascimento, Thiago; Ekeledo, Obioma J.; Anderson, Ruchi; Le, Huy B.; Belin de Chantemèle, Eric J. (Frontiers in Physiology, 2017)
Obesity-related cardiovascular disease (CVD) involves increased sympathetic activity in men and male animals. Although women exhibit increased visceral fat, metabolic disorders, inflammation and CVD with obesity, whether body weight gain affects autonomic control of cardiovascular function in females remain unknown. Due to the lack of adequate model to mimic the human pathology, this study aimed to develop a murine model, which would allow studying the sex-specificity of the response of the autonomic nervous system to obesity and identifying the origin of potential sex-differences. We tested the hypothesis that sexual dimorphisms in the autonomic response to obesity disappear in mice matched for changes in body weight, metabolic and inflammatory disorders. Male and female C57Bl/6 mice were submitted to control (CD) or high fat diet (HFD) for 24 weeks. Female mice gained more adipose mass and lost more lean mass than males but reached similar visceral adipose mass and body weight, as males, at the end of the diet. 24 weeks of HFD matched male and female mice for visceral adiposity, glycaemia, plasma insulin, lipids and inflammatory cytokines levels, demonstrating the suitability of the model to study human pathology. HFD did not elevate BP, but similarly increased heart rate (HR) in males (CD: 571±9 vs. HFD: 631±14 bpm, P<0.05) and females (CD: 589±19 vs. HFD: 642±6 bpm, P<0.05). Indices of autonomic control of BP and HR were obtained by measuring BP and HR response to ganglionic blockade, β-adrenergic and muscarinic receptors antagonists. HFD increased vascular but reduced cardiac sympathetic drive in males (CD: -43±4 and HFD: -60±7% drop in BP, P<0.05). HFD did not alter females’ vascular or cardiac sympathetic drive. HFD specifically reduced aortic α-adrenergic constriction in males and lowered HR response to muscarinic receptor antagonism in females. These data suggest that obesity-associated increases in HR could be caused by a reduced cardiac vagal tone in females, while HR increases in males may compensate for the reduced vascular adrenergic contractility to preserve baseline BP. These data suggest that obesity impairs autonomic control of cardiovascular function in males and females, via sex-specific mechanisms and independent of fat distribution, metabolic disorder or inflammation.